Pengaruh Lingkungan Pembelajaran terhadap Children Well-Being di TK Al-Husna - Rifa Mahmudah; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze the influence of the learning environment on children's well-being at Al-Husna Kindergarten. The learning environment in this study encompasses the physical, social, and emotional aspects experienced by children during learning activities. The method used is a quantitative approach with a survey design, involving a number of children as research subjects selected purposively. Data collection was carried out through observations and questionnaires tailored to the characteristics of early childhood, then analyzed using descriptive and inferential statistical techniques. The results of the study indicate that a conducive, safe, and enjoyable learning environment has a positive and significant influence on children's well-being, which is characterized by increased feelings of comfort, happiness, involvement, and social interaction skills. In addition, responsive teacher support and harmonious social relationships also strengthen these positive impacts. Based on these findings, it is recommended that early childhood education institutions pay more attention to structuring child-friendly learning environments, improving the quality of interactions between teachers and children, and creating an inclusive and supportive learning atmosphere to optimize children's well-being in the learning process